c.1 - "Chopra, Sanjeev (ed.)" (Dehradun, 1999)
This book is about Co-operatives: Policy Issues for the SAARC Region published in association with the Centre for Co-operatives and Rural Development, LBS National Academy of Administration.
Keywords: Cooperatives